2013
DOI: 10.1530/joe-13-0199
|View full text |Cite
|
Sign up to set email alerts
|

Gliquidone decreases urinary protein by promoting tubular reabsorption in diabetic Goto-Kakizaki rats

Abstract: The efficacy of gliquidone for the treatment of diabetic nephropathy was investigated by implanting micro-osmotic pumps containing gliquidone into the abdominal cavities of Goto-Kakizaki (GK) rats with diabetic nephropathy. Blood glucose, 24 h urinary protein, and 24 h urinary albumin levels were measured weekly. After 4 weeks of gliquidone therapy, pathological changes in the glomerular basement membrane (GBM) were examined using an electron microscope. Real-time PCR, western blotting, and immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The increase in these proinflammatory mediators has also been consistently reported in previous studies using the GK rat and is considered a mainstay in the T2DM condition (18,22,30). Although outside the scope of this study, previous studies have also taken urine measurement of the GK and found increased albumin, advanced glycation end products, creatinine, and protein (3,27,50,58), which is also seen in individuals with T2DM (12), further supporting…”
Section: A B Csupporting
confidence: 87%
“…The increase in these proinflammatory mediators has also been consistently reported in previous studies using the GK rat and is considered a mainstay in the T2DM condition (18,22,30). Although outside the scope of this study, previous studies have also taken urine measurement of the GK and found increased albumin, advanced glycation end products, creatinine, and protein (3,27,50,58), which is also seen in individuals with T2DM (12), further supporting…”
Section: A B Csupporting
confidence: 87%
“…There is a lack of studies about the renal effects of sulphonylureas on DCKD. Very recently, an experimental study has investigated the effect of implanting micro-osmotic pumps containing gliquidone into the abdominal cavities of rats with DN [ 23 ]. When compared to control or to rats treated with insulin, these authors detected that gliquidone treatment effectively reduced urinary protein.…”
Section: Older Hypoglycemic Treatments and Nephroprotectionmentioning
confidence: 99%
“…For the present study, rhGLP‐1 (7–36; beinaglutide) was purchased from Shanghai Benemae Pharmaceutical Corporation (Shanghai, China). rhGLP‐1 is an analog of native GLP‐1, and its half‐life in blood is approximately 2 h.…”
Section: Methodsmentioning
confidence: 99%
“…Blood was taken from the caudal vein, and blood glucose of >16.7 mmol/L for three consecutive days after the second STZ injection is considered the standard of a diabetic model. All the diabetic rats were fed with conventional chow for an additional 8 weeks. Then, 24 diabetic rats were divided into the three groups according to a random number‐generating table ( n = 8) as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation